2014
DOI: 10.17221/7382-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of bilateral polydactyly in a dromedary camel: a case report

Abstract: ABSTRACT:The following case report describes the diagnosis and surgery of bilateral polydactyly of unknown origin in a dromedary camel. A two-year-old, 290 kg, intact female camel was admitted for surgical removal of bilateral supernumerary digits associated with the medial aspects of the metacarpi and proximal to the fetlock joints. Radiographic examination revealed bilateral polydactyly with complete fusion of metacarpal bones. Surgery consisted of an osteotomy of surplus metacarpal bones combined with amput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…To the authors’ knowledge, this is the first reported case where MRI and ultrasound have been used to better understand an equine supernumerary digit excision and the first case where the long‐term outcome (8 years) is provided. Polydactyly is usually easily diagnosed by clinical examination and definitive diagnosis is made with radiographs (Ahmed ). Polydactyly can be associated with abnormalities in the carpal bones (Barber ); therefore, radiographs should include the metacarpus II, metacarpus IV and the carpus.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors’ knowledge, this is the first reported case where MRI and ultrasound have been used to better understand an equine supernumerary digit excision and the first case where the long‐term outcome (8 years) is provided. Polydactyly is usually easily diagnosed by clinical examination and definitive diagnosis is made with radiographs (Ahmed ). Polydactyly can be associated with abnormalities in the carpal bones (Barber ); therefore, radiographs should include the metacarpus II, metacarpus IV and the carpus.…”
Section: Discussionmentioning
confidence: 99%
“…Polydactyly is commonly reported in domestic species, including dogs (Paryani, 2015), ruminants (Al-Ani, Hailat, & Fathalla, 1997), horses (Carstanjen, Abitbol, & Desbois, 2007;Stanek & Hantak, 1986), and camels (Ahmed, 2014). Considerable diversity in polydactylous phenotypes has been described in cats (Danforth, 1947;Hamelin, Begon, Conchou, Fusellier, & Abitbol, 2017;Lettice, Hill, Devenney, & Hill, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Palec dodatkowy najczęściej występuje po przyśrodkowej stronie kończyny piersiowej, ale zdarzają się również przypadki deformacji po stronie bocznej lub po obydwu stronach kończyny. Może pojawić się w jednej, w dwóch albo we wszystkich czterech kończynach (1,7).…”
unclassified
“…Analogiczne deformacje rozpoznawane są również u wielu innych gatunków, w tym innych zwierząt kopytnych, m.in. wielbłądów (1). Wśród podobnych wad wrodzonych opisany został m.in.…”
unclassified